The Transformation of Public Relations Roles in Crisis Communication in the Social Media Era - M. Munif (CV. Agrapana Media, 2025)
The transformation of the public relations (PR) role in crisis communication has become a strategic issue in managing educational institutions in the era of social media. Advances in communication technology present new challenges, where the flow of information moves rapidly, openly, and beyond the full control of institutions. This study aims to analyze how PR adapts in managing public communication and reputation crises through the use of social media as the main platform. The method used is library research by reviewing literature related to educational public relations, social media, crisis communication, and the dynamics of digital transformation. The findings show that PR no longer functions merely as an information disseminator, but rather as an active, responsive, and data-driven public relations manager. PR professionals must possess digital competencies such as creative content production, audience analysis, and real-time issue and crisis mitigation. Social media offers great opportunities for institutional branding, but it also presents risks of negative issues and hoaxes that may damage reputation. Therefore, the implementation of a structured, ethical crisis communication strategy that focuses on restoring public trust is crucial. This study emphasizes that the transformation of the PR role is a key determinant in sustaining the reputation of educational institutions amid increasing competition and the complex dynamics of digital communication.